A random-walk model for helix bending in B-DNA. - Dickerson, R E (1983)
The double-helical B-DNA dodecamer of sequence d(C-G-C-G-A-A-T-T-C-G-C-G) has been refined independently from x-ray crystal structure analyses in five different variants: d(C-G-C-G-A-A-T-T-C-G-C-G) at 16 K, at room temperature, and with bound cis-diamminedichloroplatinum(II), and d(C-G-C-G-A-A-T-T-brC-G-C-G) in 60% 2-methyl-2,4-pentanediol at 20 degrees C and 7 degrees C. These helices display overall axial bends of 22 degrees, 18 degrees, 17 degrees, 14 degrees, and 3 degrees, respectively, providing an opportunity to investigate the nature of the bending process in B-DNA. Bending from one base pair to the next is best described as a stochastic or random-walk process, having forward, retrograde, and sidewise individual steps, but with an overall sense of bending. Individual steps almost always involve rolling of adjacent base pairs over one another along their long axes, not a tilting or wedge displacement that lifts neighboring base pairs apart at one end. A slight preference is observed for bending the double helix in a direction that compresses the major groove rather than the minor, and this is intuitively reasonable in view of the narrowness of the minor groove and its occupation by the spine of hydration that stabilizes the B form of DNA. This model predicts that, when DNA is wound around the nucleosome core, it should not be smoothly curved but should exhibit discrete bends every five base pairs as proposed by Zhurkin et al. [Zhurkin, V.B., Lysov, Y. P. & Ivanov, V. I. (1979) Nucleic Acids Res. 6, 1081-1096)]. Sharper bends may occur at alternate positions, where the major groove faces the nucleosome core.